Treatment of Odontogenic Phlegmon of the Maxillofacial Region (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Phlegmon MFA frequently presents as a condition affecting multiple pathways in the homeostasis system, including immunity, detoxification, hemostasis, rheology, etc. Gross disorders of regulation and metabolism that result in a violation of homeostasis, "disruption" of protective systems and functions, and the creation of vicious autocatalytic circles that foster the maintenance and advancement of end toxemia are the hallmarks of the development of endogenous intoxication syndrome in purulent-inflammatory diseases. The treatment of odontogenic phlegm in the maxillofacial region is the subject of this article.